Pengembangan Bisnis UMKM Produk Khas Desa Wangunsari - Inayati Nasrudin; Novi Mardiana; Nurwathi; Azwar, Ade Geovania; Ahmad Munandar; Djoko Pitoyo; Nurbani, Sofiani Nalwin; Dyah Kusumastuti (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
MSMEs are one of the business sectors in Indonesia that are able to survive amidst the pandemic and weakening global economic conditions. One of these MSME groups is the Kecimpring MSMEs in Wangunsari Village, Sindangkerta District, West Bandung Regency. Wangunsari Village is located in a very strategic area as it is an alternative route for tourists to and from Lembang. Apart from this, the quality and variety of Kecimpring products, a typical Sundanese food, is an added value to the development potential of this business. See this valuable potential, it is necessary to make sustainable development efforts such as supporting the production process, optimising inventory, improving packaging and digital marketing. Sangga Buana University's Industrial Engineering study programme, which has resources in product development, production management and digital marketing, is trying to play an active role in the evolving MSMEs in Wangunsari village. This active role is excecuted under the umbrella of Community Service (PKM) activities initiated by a team from the Faculty of Engineering, Sangga Buana University, in collaboration with the Wangunsari Village Government. The coaching activities will take the form of conducting focus group discussions on the importance of digital marketing for MSME stakeholders. It is imminent that the understanding gained by the MSME players about digital marketing can encourage the MSME players to start moving towards the use of digital media in the marketing of their products to a far-reaching area. Keyword : MSMEs, Business Development, Digital Marketing, AIDA Method, Focus Group Discussion